Analisis Status Gizi Siswa Kelas 4A SD 064981 Cempaka Raya Berdasarkan Tinggi dan Berat Badan dan Pola Konsumsi Jajanan - Sudana Fatahillah Pasaribu; Tuty Hertati Purba; Febry Lesmana Putri; Dwitri Amalia Susanti; Dhea Syafitri; Tri Cahyani Lase; Farhatun Nurha; Etika Lase (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The nutritional status of primary school-aged children is an important indicator for monitoring their growth and development. This study aims to describe the nutritional status of the 4A grade students at SD 064981 Cempaka Raya based on anthropometric data and analyze the relationship between their consumption of school snacks and their nutritional status categories. The research method used is quantitative descriptive with total sampling of 20 students. Data was collected through measurements of height and weight, which were then processed using the WHO Anthro Plus software to determine the students' nutritional status categories. The measurement results show that 25% of the students are categorized as undernourished, 50% are within normal nutritional status, 20% are overweight, and 5% are obese. Bivariate analysis using the Chi-Square test revealed a highly significant relationship (p<0.001) between snack consumption patterns at school and nutritional status. The results show that all students who have the habit of consuming snacks are more likely to be categorized as overweight or obese, while students who do not consume snacks tend to be in the undernourished or normal category. These findings indicate that snack consumption patterns can be a risk factor for excess nutrition in children. Therefore, it is crucial to educate students about the importance of balanced and healthy eating habits from an early age. Monitoring snack consumption at school is also necessary to minimize the risk of obesity and excess nutrition in children. Preventive measures like these are expected to prevent health issues related to nutrition and promote healthy and optimal growth in children. By encouraging good eating habits, we can help create a healthier generation and reduce the risk of nutrition-related diseases.